2016
DOI: 10.1002/qua.25184
|View full text |Cite
|
Sign up to set email alerts
|

Geometric and electronic structures of silicon fluorides (N = 4 – 6) and potential energy surfaces for dissociation reactions → SiF4 + F and →  + F

Abstract: The geometric and electronic structures of a series of silicon fluorides SiFnfalse(n−4false)− (n = 4 − 6) were computationally studied with the aid of density functional theory (DFT) method with B3LYP and M06‐2X functionals and coupled cluster (CCSD and CCSD(T)) methods with 6‐311++G(d,p) basis set. The nature of the Si‐F bonds in these compounds was analyzed in the framework of the natural bond orbital theory and natural resonance theory. Energy characteristics (heats of reactions and energy barriers) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The formation of a shorter H-bond to the axial position of SiF 5 – than the equatorial position (1.88 vs 2.31 Å) in the C s global minimum monohydrate structure is consistent with the charge distribution on the F centers. A natural bond orbital (NBO) analysis has shown that there is a slightly greater concentration of negative charge on the axial F atoms …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of a shorter H-bond to the axial position of SiF 5 – than the equatorial position (1.88 vs 2.31 Å) in the C s global minimum monohydrate structure is consistent with the charge distribution on the F centers. A natural bond orbital (NBO) analysis has shown that there is a slightly greater concentration of negative charge on the axial F atoms …”
Section: Resultsmentioning
confidence: 99%
“…For the SiF 5 – (H 2 O) 1 system, the identified C 2 v DI 1 minimum features a typical, symmetric DIHB with the water molecule bridging two equatorial F atoms of the anion. Because of the anion’s trigonal bipyramidal structure with slightly more negative charge accumulated on the axial F atoms, another unique monohydrate minimum was identified in which water binds in an asymmetric DIHB motif with one axial and one equatorial F atom. Interestingly, this second minimum, C s DI 1 , has an electronic energy that is more than 2 kcal mol –1 lower than that of the C 2 v DI 1 local minimum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of six‐fold‐coordinated Si atoms, the 3 s, 3p, and 3d atomic orbitals hybridize to form sp 3 d 2 hybrid orbitals. The four valence electrons of a Si atom and the four valence electrons of four ligand atoms are shared, forming four covalent bonds, whereas the remaining two hybrid orbitals are occupied by two electron pairs donated by two ligand atoms and form two covalent bonds, as in the SiF 6 2− ion of hexafluorosilicic acid (H 2 SiF 6 ) [31,32] . Therefore, the SiO 6 units are dianionic in nature (expressed as (SiO 6/2 ) 2− ), and two positive charges are required to compensate for the formation of each (SiO 6/2 ) 2− unit [28] .…”
Section: Figurementioning
confidence: 99%
“…The four valence electrons of a Si atom and the four valence electrons of four ligand atoms are shared, forming four covalent bonds, whereas the remaining two hybrid orbitals are occupied by two electron pairs donated by two ligand atoms and form two covalent bonds, as in the SiF 6 2À ion of hexafluorosilicic acid (H 2 SiF 6 ). [31,32] Therefore, the SiO 6 units are dianionic in nature (expressed as (SiO 6/2 ) 2À ), and two positive charges are required to compensate for the formation of each (SiO 6/2 ) 2À unit. [28] In H 5 Si 2 P 9 O 29 glass, only protons that bind to the NBOs of PO 4 units surrounding Si (6) atoms (i. e., Q 3 (1Si) units) and form OÀ H bonds can be involved in charge compensation.…”
mentioning
confidence: 99%